People’s Perception on Multilingual Education: A study of Tamang Language based Multilingual School - Bishowkarma, Aita (Rainbow Journal, 2019)
Recent discourse on multilingual education largely has been dominated by the perception of people in the areas of policy and practice. There has been inadequate research on the education and schooling of Tamang children from a critical perspective. This study explores the perceptions of stakeholders on Tamang language-based multilingual education (MLE) practised in Nepal. This paper critically examines the perception of stakeholders and pedagogical practices in the classroom from the perspective of access to quality education to Tamang children in a primary school in Nepal. The qualitative data were generated from the policy makers, experts, head teachers and parents purposively selected from two Tamang language-based schools in Rasuwa. The data was generated from MLE practitioners through interview were analyzed triangulating the theoretical lens and discussed applying descriptive and exploratory methods. The findings reveal that current practices of multilingual; education is inadequate to ton provide access to quality education to Tamang children due to the inefficient pedagogical practices people’ perceptual value on standard language. The stakeholders have diverse perceptions regarding the access to quality education to Tamang children from mother tongue-based multilingual education. The findings imply enhancing Tamang language-based multilingual schools.